Teaching speaking in Kampung Inggris: the tutors’ challenges and solutions - Andriani, Agis; Abdullah, Fuad; Hidayati, Arini Nurul; Syafira, Noer Aini Nanda (Intelektual Pustaka Media Utama, 2024)
Teaching English speaking has become a centre of attention among scholars and teaching English to speakers of other languages (TESOL) practitioners for a few decades. However, the issue of teaching English speaking in Kampung Inggris/English Village remains under-researched, notably viewed from the tutors’ challenges and solutions in the Indonesian English as a foreign language (EFL) milieu. This study addressed this gap. Two English tutors from Kampung Inggris/English Village got involved as the participants. The data were collected through semi-structured interviews and analyzed with thematic analysis. The findings reported that there were five challenges encountered by tutors when teaching English speaking, namely tutors' inability of exploring English language teaching materials, tutors' insufficient English vocabulary, tutors' ineffective time management during language teaching practices, demotivated tutees to learn English, and perceived teaching anxiety. In addition, the tutors stipulated four solutions to cope with such challenges, namely building a good rapport between tutor and tutees, tutors' self-motivation to English vocabulary enrichment, selecting appropriate and providing updated English language teaching materials, and motivating English language tutees. Therefore, teaching English speaking should not only rely on immersing students in fluency-based activities but also manage tutees' psychological factors to attain more effective teaching English speaking objectives.